Potret Isu Pelayanan Publik dan Tingkat Pengenalan Lembaga Ombudsman Perwakilan dalam Perspektif Big Data - Andi Setyo Pambudi; Istiqlal Abadiyah Sukma Putri; Devy Paramitha Agnelia (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2022)
Public service providers and their supervisory agencies (Ombudsman RI), both at the centre and the representatives, are required to be able to map and resolve public service issues. However, during the Covid-19 they are limited in scope for conducting investigations. Big data is considered one of the solutions to obtain information on the priority scale of handling public service supervision through strategic issues of public services that get lots of attention from the public and the media. This paper aims to present a portrait of public service issues and the recognition rate of the Ombudsman Representative in the big data perspective as input in development planning related to public service supervision. The analytical method used is big data which utilizes the Intelligence Media Analytics developed by Indonesia Indicator. Analysis of strategic issues of public service in the regions, types of problems, the reported agencies, and the level of popularity of the Ombudsman RI in representatives in the community and the media, are the main discussion in this analysis. The results show that based on the classification of the reported parties, the three agencies that received the highest complaints during the period March 2020 – March 2021 are the Social Affairs Agency, Education Agency, and Health Agency. Problems related to Social Assistance were the most widely reported complaints by the public to the Ombudsman RI during the Covid-19. In addition, the analysis shows that until the latest data in 2021, the level of popularity of the Ombudsman in the regions is still low.